One Year Review of Maternal Mortality Associated With Eclamsia in a Tertiary Care Level Hospital (Journal of Chittagong Medical College Teachers' Association, 2013)
To enlist the causes of maternal death in patients of eclampsia and to determine how sociodemograpphic and clinical characteristics of the women influence the death in eclampsia in our setup. This study was conducted in obstetrics and gynaecology department of Chittagong Medical College Hospital, Chittagong, from January 2011 to December 2011. Patients were admitted through emergency obstetrics care unit. Patients demographic record including age, parity, education, socio-economic status along with antenatal care records, level of care and distance from hospital number of fits, gestational age, type of eclampsia, presence of complications, mode of delivery and causes of death were analyzed. All this information was collected from patients records. Eclampsia accounted for 38 (37.7%) of the 101 total maternal deaths recorded within the 1 year period, with case fatality of 9.9%.All patients were unbooked and majority were primigridia(63%) and less than 20 years(39%). Education and socioeconomic status were poor. Ante partum eclampsia was the cause in 78.9% and 5.2% of the pregnancies were not delivered before their death. Overall 23% patients had at least one complications and the remaining 67% had more than one complications. The complications leading to eventual death were pulmonary oedema 7(18.4%), LVF 6(15.7%), CVD 6(15.7%), Multiorgan failure 6(15.7%), HELLP 4(10.5%), DIC 3(7.8%), Renal failure 3(7.8%), peroperative cardiac arrest 2(5.2%) and pulmonary embolism 1(2.6%). The distance from the hospital was 10km to 150km. The level of care at nearest health facilities were estimated.52.6% was attended by traditional birth attendant, 6.9% by skilled birth attendants, 2.9% by doctors and for 25.7%, no level of care was available. Eclampsia stil remains the major cause of maternal mortality in our setup resulting from unsupervised pregnancies and deliveries. There is need to educate and encourage the general public for antenatal care and hospital delivery.JCMCTA 2012 ; 23 (2): 30-33